INTEGRATION OF CHATGPT APPLICATION IN MADRASAH IBTIDAIYAH LEARNING: A STUDY OF ACADEMIC ETHICS AND ITS IMPACT ON STUDENTS' READING LITERACY - Khotimah, Khusnul; Ishari, Nurhafid; Darajat, Muhaiminah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research is motivated by the importance of understanding the use of language in political communication in digital media, especially expressive speech that not only conveys information, but also shows the attitude and feelings of the speaker. The problem in this study is how the function of expressive speech is used in political discussions on YouTube and how it plays a role in building meaning and influencing the audience. This study aims to identify and analyze the function of expressive speech in Gita Wirjawan's YouTube video entitled